2009
DOI: 10.1111/j.1752-1688.2009.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Constraints to Watershed Planning: Group Structure and Process1

Abstract: Floress, Kristin, Jean C. Mangun, Mae A. Davenport, and Karl W.J. Williard, 2009. Constraints to Watershed Planning: Group Structure and Process. Journal of the American Water Resources Association (JAWRA) 45(6):1352‐1360. Abstract:  The roles that agencies and other partners play in collaborative watershed management are not always clearly identified. Key factors contributing to group‐level outcomes in watershed groups include both structural and procedural elements. Structural elements include membership sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…For instance, a landowner survey in an impaired watershed revealed that while respondents felt obligated to protect water on their own land, they felt significantly less obligated to talk to others about water resource problems or to work with other community members to protect water in the community (Davenport et al, 2013). Studies also have shown that citizen-based watershed groups designed to promote civic engagement have had difficulty sustaining member involvement and interest (Koehler and Koontz, 2008;Floress et al, 2009). To be effective in civic engagement, water resource managers need a better understanding of what drives and constrains civic engagement in environmental decision making.…”
Section: Collaborative Watershed Management and Civic Engagementmentioning
confidence: 99%
“…For instance, a landowner survey in an impaired watershed revealed that while respondents felt obligated to protect water on their own land, they felt significantly less obligated to talk to others about water resource problems or to work with other community members to protect water in the community (Davenport et al, 2013). Studies also have shown that citizen-based watershed groups designed to promote civic engagement have had difficulty sustaining member involvement and interest (Koehler and Koontz, 2008;Floress et al, 2009). To be effective in civic engagement, water resource managers need a better understanding of what drives and constrains civic engagement in environmental decision making.…”
Section: Collaborative Watershed Management and Civic Engagementmentioning
confidence: 99%
“…As our communities grapple with critical water resource management issues—including drought response, water conservation, water quality impairment, climate change, agricultural and landscape irrigation, and environmental flows and water rights—it is increasingly important to provide key water resource information to citizens, enabling them to make informed water‐use decisions (Floress et al, 2009; Rosenzweig et al, 2007; Willis et al, 2011). Based on state‐level needs assessments that identified water resource status and management as a priority for extension programs, extension services and land‐grant institutions (LGIs) have directed human and financial resources toward providing education for the public regarding water use efficiency, water quality, and environmentally sustainable practices.…”
mentioning
confidence: 99%
“…This study was designed to incorporate the opinions of a diverse group of randomly selected stakeholders, so that the results more accurately reflected the opinions of the region as a whole, rather than those of special interest groups, which has been noted as a shortcoming in previous studies focused on incorporating stakeholder opinions into watershed management (Chess et al ., ; Larson and Lach, ; Floress et al ., ). The results of this study show that general public participants identified regulating ecosystem services with varying levels of spatial accuracy, with only flood protection (78.37%) and water quality protection (73.45%) approaching the accuracy reported in previous studies by Brown () on participant identification of native vegetation in New Zealand (95.8%) and Cox et al .…”
Section: Resultsmentioning
confidence: 97%